Analysis of the Factors that Affect to Visited Interest to the Kolam Pancing and Warung Lesehan “CSDW” in the Kalipecabean Village, Candi Subdistrict, Sidoarjo Regency, East Java - Dwin Yolandari Makhfiroh (Faculty of Fisheries and Marine Science, Brawijaya University, 2017)
Kolam Pancing dan Warung Lesehan